Inducing aggresome and stable tau aggregation in Neuro2a cells with an optogenetic tool - Shigeo Sakuragi; Tomoya Uchida; Naoki Kato; Boxiao Zhao; Toshiki Takahashi; Akito Hattori; Yoshihiro Sakata; Yoshiyuki Soeda; Akihiko Takashima; Hideaki Yoshimura; Gen Matsumoto; Hiroko Bannai (Biophysics and Physicobiology)
Tauopathy is a spectrum of diseases characterized by fibrillary tau aggregate formation in neurons and glial cells in the brain. Tau aggregation originates in the brainstem and entorhinal cortex and then spreads throughout the brain in Alzheimer’s disease (AD), which is the most prevalent type of tauopathy. Understanding the mechanism by which locally developed tau pathology propagates throughout the brain is crucial for comprehending AD pathogenesis. Therefore, a novel model of tau pathology that artificially induces tau aggregation in targeted cells at specific times is essential. This study describes a novel optogenetic module, OptoTau, which is a human tau with the P301L mutation fused with a photosensitive protein CRY2olig, inducing various forms of tau according to the temporal pattern of blue light illumination pattern. Continuous blue light illumination for 12 h to Neuro2a cells that stably express OptoTau (OptoTauKI cells) formed clusters along microtubules, many of which eventually accumulated in aggresomes. Conversely, methanol-resistant tau aggregation was formed when alternating light exposure and darkness in 30-min cycles for 8 sets per day were repeated over 8 days. Methanol-resistant tau was induced more rapidly by repeating 5-min illumination followed by 25-min darkness over 24 h. These results indicate that OptoTau induced various tau aggregation stages based on the temporal pattern of blue light exposure. Thus, this technique exhibits potential as a novel approach to developing specific tau aggregation in targeted cells at desired time points.